Concentration of Rhenium-188 for the Radiopharmaceutical Synthesis - A. O. Malysheva; G. E. Kodina; E. A. Lyamtseva (Разработка и регистрация лекарственных средств)
Introduction. Rhenium-188 has found wide application in nuclear medicine for the treatment of metastatic lesions of the skeletal system and joint diseases such as rheumatoid arthritis and synovitis. Also, 188Re-radiopharmaceuticals are being developed for the palliative treatment of hepatocellular carcinoma and others. Immediately after the first clinical trials of 188Re-radiopharmaceuticals, when information on clinically effective administered doses for radionuclide activity was obtained, the use of sodium perrenate, 188Re solutions with high volume activity for radiopharmaceutical synthesis and, consequently, additional concentration of obtained from the generator solutions became extremely relevant.Aim. Development of the technique for concentration of sodium perrenate, 188Re solution, obtained from the 188W/188Re generator "GREN-1" (State Research Center of the Russian Federation IPPE named after Leipunsky, Obninsk, Russia) under laboratory conditions, and comparison of the quality indicators of the resulting product and Na188ReO4 solution obtained from the generator with an automatic concentration module NEPTIS-TH (IRE, Belgium).Materials and method. The objects of this study were eluates from the 188W/188Re generator "GREN-1" manufactured by the IPPE JSC (Obninsk, Russia) and the materials used in the production and quality control of these generators, as well as the generator produced by the National Institute of Radioelements (IRE, Belgium) with an automatic concentration module NEPTIS-TH. The following methods were used to control the quality of sodium perrhenate, 188Re solutions: radiometry, thin layer chromatography, potentiometry, potentiometric titration, atomic absorption spectroscopy.Results and discussion. The efficiency of concentration of the eluate from the "GREN-1" generator using cartridges filled with cation exchanger Dowex® 50WX8 (100–200 mesh) (Sigma-Aldrich, USA, Cat. No. 217506) and Al2O3 with pH 4 (100–200 mesh), and the IRE generator using the automatic NEPTIS-TH module was studied. The yield of rhenium-188 after concentration was 75–85 %. As a result of the concentration process, there is no proportional increase in the content of chemical impurities, and it is possible to obtain cleaner solutions for the content of metals such as Fe, Zn, Cu and others. It was found that in the routine use of generators, the value of the volume radioactivity of the obtained concentrated sodium perrhenate, 188Re solution should not exceed 7.4–8.0 GBq/ml.Conclusion. The conducted studies have shown that the task of concentration of sodium perrenate, 188Re solutions with high volume activity of appropriate quality for the preparation of radiopharmaceuticals for radionuclide therapy can be solved using quite affordable materials, namely a sequence of cartridges. The use of an automatic module is more preferable than the use of manual assembly of a sequence of cartridges, based on the guaranteed quality assurance of the resulting sodium perrenate, 188Re solution and reducing the dose burden on personnel. However, the conducted studies have shown that the tested concentration module is incompatible with the domestic generator, so the system proposed for the study was not registered in Russia. The results obtained in this work will be used to organize the industrial production of domestic modules and cassettes in complete set with "GREN-1" generator.